A study of the wound performance following subcutaneous infiltration and topical instillation of ceftriaxone before primary closure of skin in laparotomy for peritonitis due to non-traumatic perforation of small intestine - S., Sudhir; Telkar, Kanmani G. (International Surgery Journal, 2017)
Background: Surgical site infection (SSI) continues to be a baffling problem since time immemorial. It is one of the major causes for postoperative morbidity and mortality. Many methods have been evolved to combat wound infection, but the rate of wound infection has been more or less static over past few years. The search for alternative modes of management is going on and one of the methods is intra incisional subcutaneous infiltration of antibiotics. Methods: This is a prospective study comprising of control and study groups of 25 patients each. Control group patients did not receive subcutaneous infiltration of 1gm (diluted with 10 cc of distilled water) of ceftriaxone whereas study group received the infiltration. Precise examination of wound was done from post-operative day 3 up to day 10 for the presence of pus discharge or any subcutaneous collection. Results: Wound infection rate was 48% in control group and 32% in study group that is 12 out of 25 patients wound were infected in control and 8 out of 25 were infected in study group and 13 out of 25 had no infection in control and 17 out of 25 had no wound infection in study group. Conclusions: The incidence of SSI in the group which received subcutaneous infiltration of antibiotic was less than the group of patients, which did not receive ceftriaxone, showing that the use of subcutaneous infiltration of ceftriaxone injection at the time of wound closure may be more effective in reducing SSI.